Crime, social disorganization, and social structure: A research note on the use of interurban ecological models - Petee, Thomas A. (American journal of criminal justice, 1994)
The social disorganization perspective, as set forth by Clifford Shaw and Henry McKay, has enjoyed renewed interest in criminological explanations of crime and delinquency. This paper extends this perspective beyond the traditional intraurban focus of the neighborhood to a more encompassing interurban model, using 682 SMSA counties. The results using these counties were generally consistent with neighborhood studies, demonstrating the robustness of the social disorganization model.